A New Perspective for Second Language Acquisition: Parsing - Bourdages, Johanne (Revue québécoise de linguistique, 1991)
AbstractThe focus of this paper is on the possible contribution of research in Parsing Theory to the field of Second Language Acquisition. The aim of this paper is an examination of the relationship between the parsing mechanism and the process of language acquisition, and, more specifically, second language acquisition. The suggestion is made that this framework is a valid and an interesting one to pursue in that it might provide evidence to support current hypotheses in Parsing Theory and in Second Language Acquisition.